Représenter le sens d’un adjectif polysémique dans une perspective bilingue — la quête de l’équivalence - Perz, Magdalena (Neophilologica, 2018)
This study seeks to approach the problem of disambiguation of adjectives in the context of translation. On the basis of the French adjective austère analyzed as a case of study, the author demonstrates that adjectives can have a few equivalents in the Polish language. Such multiple interpretations caused by polysemy can be a problem for the description of adjectives in lexicographical publications, as well as for translation. Correspondences between adjectives are rarely bi-univocal in two languages and this study gives some insights on the possibilities of using this terms in both languages. Differences between senses are often highly subtle and contextually determined, so the author makes use of the theory of classes of objects. This kind of complex description allows to select the correct equivalent in another language and to make explicit the relations of equivalence between two languages.